Analysis of mood states, trait anxiety, and state anxiety: A study with athletes before artistic gymnastics competitions - Patrícia, Barreto Marques [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP]; Filho, Dalton Müller Pessôa [UNESP]; Merussi, Neiva Cassiano [UNESP] (My University, 2019)
The objective of the present study was to analyze and associate the scores related to mood, trait anxiety, and state anxiety in artistic female gymnasts moments before sports competitions. The sample consisted of 80 female gymnasts with an average age of 13.2 ± 2.1 years of age. The athletes were selected at random and oriented to individually answer the following questionnaires at the venue of artistic gymnastics competitions 30 minutes before their performances: Competitive State Anxiety Inventory-2 (CSAI-2), to measure precompetitive state anxiety; Sport Competition Anxiety Test (SCAT), which provides a competitive trait anxiety measure; and the Brunel Mood Scale (BRUMS), to measure mood states. Most of the participants showed trait anxiety classified as intermediate to high (47.5 %), and cognitive state anxiety (47.5 %), somatic state anxiety (56.2 %), and self-confidence (43.7 %) being classified as intermediate. Concerning total mood disorder (TMD), 37 participants (46.2 %) were classified as having high TMD in comparison to the population studied. It can be concluded that the athletes evaluated in the present study showed low vigor levels and high tension and fatigue levels before artistic gymnastics performances.
Keywords: Anxiety; Artistic gymnastics; Competition; Mood